Experience, narrative, and criticism in ancient Greece under the spell of stories - Grethlein, Jonas 1978-; Huitink, Luuk 1981-; Tagliabue, Aldo 1982- (Cognitive classics, 2020)
Drawing on cognitive approaches to literary studies, this volume pursues a new approach to ancient Greek narrative that transcends the taxonomies of structuralist narratologies, deploying concepts such as immersion and embodiment in order to establish a more comprehensive understanding of ancient Greek narrative and ancient reading habits